Community Structure on Seagrass Fish Resources at Pandaratan Beach, North Sumatra : Struktur Komunitas Sumberdaya Ikan Padang Lamun di Pantai Pandaratan, Kabupaten Tapanuli Tengah, Provinsi Sumatera Utara - Pulungan, Ahyar; Inrika, Huwilda; Fadhilah, Amanatul (Tropical Fisheries Management Journal, 2020)
Seagrass beds are potential marine resources to be utilized, and ecologically, seagrass beds are some of the important functions of the coastal area. Many organisms are ecologically and biologically very dependent on the presence of seagrasses. The ecosystem is an important food source for the organism by many sea organisms that use it as a spawning place. This study aims to determine the diversity of fish in seagrass beds in Padaratan Beach, Sarudik Subdistrict, Central Tapanuli Regency. A gillnet is used to obtain fish samples at three observation stations during the period from mid-March to April 2018. Fish diversity can be agreed by looking at the composition of fish species and diversity index. The results of this study show the total number of fish obtained, 196 individuals, consisting of 12 families and 14 species. The highest number of fish catches is at Station II with a total catch of 70 individuals. The highest relative abundance of stations I, II, and III with values â€‹â€‹of 22.96%, 20.01%, and 23.07% are found in fish species from the family Hemaramphidae with Zenarchopterus gilli species. The diversity index value (H') of all observation stations shows that species richness is in a moderate condition with values â€‹â€‹of the station I (2,339), station II (2,439) and station III (2,367). While the uniformity value (e), shows the value of station I (0.866) station II (0.924) and station III (0.897) observations are in a stable condition (0.75 <e d â€1.00). Such conditions indicate that the distribution at each observation station is equitable.